DIFFERENT STRATEGIES OF TEACHING ACADEMIC VOCABULARY FOR EFL LEARNERS - Utaganova, Roza Mamadiyor qizi (Educational Research in Universal Sciences, 2023)
Today, English language has been playing an important role in different disciplines in both academic and daily life in order to communicate orally or in a written discourse throughout the world. Not only learning English itself, but also acquiring any kinds of foreign language requires to know plethora of vocabularies in both academic and casual style to convey the message in spoken and written discourse. Specifically, academic vocabulary learning is one of the most valuable aspects of learning language in terms of using in different programs or subjects. Nation (2001) states that being aware of academic vocabulary and ability to comprehend and being able to implement it in writing is an important tool for students in English for Academic Purpose (EAP) programs. In this work, different strategies and various methods, tools, and approaches are discussed about how to teach ESP vocabulary for different age group of people.